EVALUASI KEBIJAKAN PERATURAN WALIKOTA SEMARANG N0. 05 TAHUN 2013 TENTANG PENATAAN TOKO MODERN MINIMARKET KOTA SEMARANG (Studi di Kecamatan Banyumanik Kota Semarang) - Dany Widiastuti; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The Government of Semarang city publish the ordinance mayor of Semarang number 5 in 2013 about a regulation of modern shop or Minimarket in Semarang as One Effort to resolve proliferation minimarket problems in Semarang. The low level of protection toward Traditional markets, shops/stalls against the existence of modern shops minimarket in District Banyumanik, that be background of research. The research is aimed to evaluate Implementation the ordinance mayor of Semarang number 5 in 2013 about a regulation of modern shop or Minimarket in district Banyumanik, Semarang. the implementer in this policy is the Department of Trade and Investment Agency Services Integrated One Door Semarang. The research use Evaluation indikator by William N. Dunn like effectiveness, Adequacy, Equity, Responsiveness and Appropriateness. The Research method is qualitative and the data collection techniques are interviews, observation and documentation. The results of Evaluation that implementation of the Mayor Regulation No. 5 in 2013 about a regulation of modern shop or Minimarket in Semarang in Banyumanik district is not maximum with the goals. the distance is too close between minimarket and traditional market . then, the empowerment of traditional market, store / shop is limited and partnerships between minimarket with UMKM is not maximum. The synergies between traditional market, shops/stalls with minimarket is still bad.